Otorgamiento de permisos de aprovechamiento forestal en bosques locales en la Región Loreto – Perú - Arirama Ijuma, Juan (2014)
The experience was developed in the Regional Program for the Management of Forest and Wildlife Resources (PRMRFFS) that is part of the Regional Government of Loreto, as a technical, regulatory, and decentralized body, dependent on the Regional General Management, created by Regional Ordinance No. 017-2009-GRL-CR, September 17, 2009. The professional performance includes the evaluation of the technical file and subsequent approval for the establishment and granting of local forest management to rural populations or populated centers of the Loreto region. Since 2012 to date, 68 forest permissions have been granted in this modality of access to the forest in the entire Loreto region. Limitations and difficulties that arise in the performance of the functions include the reduced number of personnel that the PRMRFFS with especiality in the evaluation of forest management plans (PMF) and Annual Operating Plans (POA); Furthermore, the budget for visual inspections prior to the approval of the Annual Operating Plans is reduced. The proposal to overcome the limitations and difficulties is to implement a greater number of personnel for the evaluation and visual inspection of the Forest Management Plans at both levels, permanent training of the personnel and higher a budget for the execution of visual inspections prior to the approval of the Annual Operating Plans.